An accurate REDD+ reference level for Terai Arc Landscape, Nepal using LiDAR assisted Multi-source Programme (LAMP) - Joshi, A. R.; Tegel, K.; Manandhar, U.; Aguilar-Amuchastegui, N.; Dinerstein, E.; Eivazi, A.; Gamble, L.; Gautam, B.; Gunia, K.; Gunia, M.; et al. (Banko Janakari, 2015)
In preparation for participation in funding mechanisms established under the United Nations’ framework for reducing emissions from deforestation and forest degradation (REDD+), the Government of Nepal has developed a sub-national reference level (RL) for the 12 districts of Terai Arc Landscape (TAL) in partnership with the WWF-Nepal, WWF-US and Arbonaut Ltd., Finland. The reference level was established using LiDAR–Assisted Multisource Programme (LAMP), an innovative effort that utilizes existing national forest and survey data, field sampling, satellite imagery, and airborne LiDAR data to measure deforestation and forest degradation, regrowth and maintenance of forests, and the resulting emissions and sequestration of CO2 in the project districts for the period 1999–2011. This effort was designed to create a sub-national RL that meets the highest international standards for integrity and transparency and followed closely the guidelines of the Methodological Framework (MF) defined by the Forest Carbon Partnership Facility (FCPF) at the World Bank and Guidelines defined by Intergovernmental Panel on Climate Change (IPCC).The present analysis shows that during the 12-year period between 1999 and 2011 a net total of 52,245,991 tons CO2 (tCO2e) was emitted from the forest sector in the TAL, an average emission of 4,353,833 tons CO2e per year. The results presented here reflect the first iteration of the TAL RL and a major milestone in an on-going process that will further refine and improve the RL in the months ahead based on external review and input and additional field verification and data analysis. Banko Janakari, Vol. 24, No. 1, pp-23-33